2013
DOI: 10.1108/13639511311302524
|View full text |Cite
|
Sign up to set email alerts
|

Police response to domestic violence: multilevel factors of arrest decision

Abstract: PurposePolice factor in extra‐legal as well as legal context in their decision to arrest a suspect. The purpose of this paper is to examine the effect of extra‐legal factors at both situational and neighborhood levels.Design/methodology/approachUsing hierarchical generalized linear modeling, over 9,000 domestic violence cases across 421 census tracts in Houston, Texas were examined. Situational information was derived from police reports, and neighborhood factors were measured by population characteristics dra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
50
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(57 citation statements)
references
References 62 publications
5
50
2
Order By: Relevance
“…Nonetheless, previous research has concluded that the characteristics of the violent act are the most important legal factor affecting police arrest decisions. Of these characteristics, injuries resulting from the violence and the possible use of weapons have explicitly been found to be connected to the decision to make an arrest (Lee et al 2013;Phillips, 2008). Our legal factors in this study are therefore seriousness of violence and the .…”
Section: Previous Researchmentioning
confidence: 87%
See 1 more Smart Citation
“…Nonetheless, previous research has concluded that the characteristics of the violent act are the most important legal factor affecting police arrest decisions. Of these characteristics, injuries resulting from the violence and the possible use of weapons have explicitly been found to be connected to the decision to make an arrest (Lee et al 2013;Phillips, 2008). Our legal factors in this study are therefore seriousness of violence and the .…”
Section: Previous Researchmentioning
confidence: 87%
“…Factors associated with police decisions to make arrests can be roughly divided into two groups: legal and extra-legal factors (Lee, Zhang & Hoover, 2013;Stewart & Maddren, 1997), and police actions have to be, first and foremost, based on legal norms. When the police are acting according to law and other official directives its operations are legitimate and open for public debate.…”
Section: Previous Researchmentioning
confidence: 99%
“…There are an array of competing factors that may influence police officers’ behaviors, including situational characteristics, organizational characteristics, neighborhood characteristics, and officer value orientations (Brooks, 1989). Extant research indicates that the key factors related to police officers’ responses can be grouped into two categories: (a) incident-based legal factors (Hall, 2005; Phillips, 2008; Robinson & Chandek, 2000) and (b) extralegal factors (Black, 1976; J. Lee, Zhang, & Hoover, 2013; Smith & Visher, 1981).…”
Section: Police Officer Discretion and Decision-makingmentioning
confidence: 99%
“…Adherence to rules and regulations would therefore decrease officers’ levels of discretion, particularly in arrest situations (Eitle, 2005; Hall, 2005). Even with mandatory arrest policies for DV in the United States, contemporary research has found both legal and extralegal factors influence police decision-making in these cases (J. Lee et al, 2013).…”
Section: Police Officer Discretion and Decision-makingmentioning
confidence: 99%
“…These policies rely on discretionary decision making on behalf of the responding officer. In such cases, police must assess characteristics of the incident as well as a variety of risk factors that may attribute to continued victimization if an intervention is not taken (Lee and Hoover, 2013). These risk factors include the victim's level of fear, defendant's aggressive behaviors, physicality of the assault, police awareness of previous incidents between the victim and defendant, the presence of substance abuse, and the presence of a protective order (Houry et al, 2004;Trujillo and Ross, 2008).…”
Section: Police Response To Intimate Partner and Domestic Violencementioning
confidence: 99%